EFISIENSI DAN EFEKTIVITAS PELAKSANAAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERKOTAAN DAN PEDESAAN (PBB P2) DI KABUPATEN LOMBOK TIMUR (Studi Kasus Pada Kecamatan Selong) - Nova Hari Santhi; Oktamuliza Rahayu (BADAN PENERBIT STIEPARI PRESS, 2022)
The purpose of this study is to (1) determine the level of efficiency of collecting Land tax and Urban and Rural Buildings in Selong District, East Lombok Regency, (2) find out the effectiveness level of Land and Urban and Rural Building Tax Collection in Selong District, East Lombok Regency, (3) find out the factors that affect the efficiency and effectiveness of the implementation of the collection of Land and Urban and Rural Building Tax (PBB P2) in Selong District, East Lombok Regency. This type of research is a case study conducted in Selong District, East Lombok Regency. The data collection techniques used are interviews and documentation, while the data analysis techniques used are quantitative data analysis techniques. Quantitative data analysis is used to calculate the level of efficiency and effectiveness of collecting Land tax and Urban and Rural Buildings in Selong District (2015-2018). Through the interview obtained the factors affecting the efficiency and effectiveness of collecting the Land and Building Tax. The results showed that (1) the efficiency of collecting Land and Building Tax in Selong District, East Lombok Regency in 2015 was 0.621%, in 2016 it was 0.313%, 2017 was 0.526%, and in 2018 it was 0.598%. Thus the collection of Land and Building Tax in Selong District, East Lombok Regency runs very efficiently. (2) The effectiveness rate of land and building tax collection in Selong District, East Lombok Regency in 2015 was 60.56% in 2016 at 64.94%, 2017 at 66.95% and 2018 at 65.15%. Thus, the collection of Land and Building Tax in Selong District, East Lombok Regency runs quite effectively. (3) The most influencing factor in collecting land tax and urban and rural buildings in Selong district, East Lombok Regency is that with good communication, it is hoped that taxpayers can better know the importance of land and building tax revenues for the regions.